Ultrastructural effects on gill tissues induced in red tilapia Oreochromis sp. by a waterborne lead exposure - Aldoghachi, M.A.; Sofian-Azirun, Mohd; Yusoff, Ismail; Ashraf, M.A. (Elsevier, 2016)
Experiments on hybrid red tilapia Oreochromis sp. were conducted to assess histopathological effects induced in gill tissues of 96 h exposure to waterborne lead (5.5 mg/L). These tissues were investigated by light and scanning electron microscopy. Results showed that structural design of gill tissues was noticeably disrupted. Major symptoms were changes of epithelial cells, fusion in adjacent secondary lamellae, hypertrophy and hyperplasia of chloride cells and coagulate necrosis in pavement cells with disappearance of its microridges. Electron microscopic X-ray microanalysis of fish gills exposed to sublethal lead revealed that lead accumulated on the surface of the gill lamella. This study confirmed that lead exposure incited a difference of histological impairment in fish, supporting environmental watch over aquatic systems when polluted by lead.